English Pre-Service Teachers’ Instrument in Facilitating Students’ Digital Literacy - Wilujeng, Yose Rahayu; Safriani, Afida; Muhtarom, Muhtarom (English Education : English Journal for Teaching and Learning, 2023)
The advancement of technology nowadays has impacted contemporary society in many sectors. One of them is the education sector. The 21st century is regarded as the era of technology. It has helped many things in education and made teaching more exciting and effortless. Technology plays an essential role in human life. Teachers can use technology to make teaching media that can increase students’ attraction to follow the class. The research focused on analyzing digital tools that English pre-service teachers use, how it functions, how it benefits teachers and students, and how students respond to certain digital tools. This research was done by analyzing five recorded micro-teaching videos of English pre-service teacher teaching internship programs, four lesson plans, and clarified by interviewing four related English pre-service teachers. This research found that English pre-service teachers did facilitate students’ digital literacy. Students are also left with good responses towards the activity, which is shown by the recorded video where the students actively participate.